Associated Factors of Cholelithiasis among Younger Children with Sickle Cell Disease at the National Reference Center for Sickle Cell Disease in Brazzaville, Congo - Firmine Olivia Galiba Atipo Tsiba; Clément Pacha Mikia; Jennifer Armandine Elira Samba; Jade Vanessa Nziengui Mboumba; Félix Malanda; Clausina Mikolele Ahoui; Alexis Elira Dokekias (Anemia)
Introduction. Chronic hemolysis predisposes sickle cell patients to the development of gallstones. Their frequency increases with age, but they may appear early in young children. In the absence of management, they expose the patient to complications that can hinder the quality of life and sometimes even death. This survey aimed to identify the associated factors of the occurrence of cholelithiasis. Materials and Methods. It was a case-control study carried out between January 2017 and June 2022 at the National Reference Center for Sickle Cell Disease (SCD) “Antoinette Sassou N’guesso” in Brazzaville. It concerned 37 children with cholelithiasis. Sociodemographic (socioeconomic status and diet) and clinical (body mass index, frequency of vasoocclusive crises and hospitalization for vasoocclusive crises, number of blood transfusion, and chronic complications) as well as hematological examination (type of SCD and blood count in the intercritical period) and hydroxyurea treatment were compared with those of 74 children with no clinical and radiographic signs of cholelithiasis. The chi-squared statistical test and the odds ratio were used for the comparison (p < 0.05). Results. The average age was 9.70 ± 1.73 years. The 10–12 age group was the most represented (22 cases or 59.45%), followed by 7- to 9-year-olds (12 cases or 32.43%). Three children (8.10%) were 6  years old. The sex ratio was 0.68 vs. 1.38. Factors associated with cholelithiasis were low socioeconomic status (83.78% vs. 45.95%; IC 95% 1.46−3.89; p≤0.001), a higher number of blood transfusions (5.54 ± 1.22 vs. 2.46 ± 1.13; IC 95% 1.55−6.70; p≤0.001), and irregular systematic monitoring (5.54 ± 1.22 vs. 2.46 ± 1.13; IC 95% 1.55−6.70; p≤0.001). Conclusion. A national strategy to facilitate access to care for patients living with sickle cell disease is imperative. Moreover, emphasis should be placed on the prevention and early management of acute complications of SCD.